2017
DOI: 10.2147/cia.s132399
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of effects of differences in trunk posture during Fowler’s position on hemodynamics and cardiovascular regulation in older and younger subjects

Abstract: BackgroundDownward shifts in blood volume with changing position generally cause tachycardic responses. Age-related decreases in vagal nerve activity could contribute to orthostatic hypotension in older individuals. Fowler’s position is a reclined position with the back between 30° and 60°, used to facilitate breathing, eating, and other routine daily activities in frail and elderly patients.ObjectiveThis study examined whether stroke volume (SV) was higher and heart rate (HR) lower in Fowler’s position with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…During the recovery period, the pressor response was greater and more long-lasting in the older participants whereas their logRSA and logBRS were lower as reported previously ( 18 , 27 , 35 ). It has been reported that the pressor response is more significant because of decreased vascular compliance in the aged ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…During the recovery period, the pressor response was greater and more long-lasting in the older participants whereas their logRSA and logBRS were lower as reported previously ( 18 , 27 , 35 ). It has been reported that the pressor response is more significant because of decreased vascular compliance in the aged ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 82%
“…BRS was calculated using Nevrokard BRS software (Nevrokard, Izola, Slovenia). RSA and BRS were log-transformed in accordance with a previous study (27,28).…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…8 However, as shown in the previous studies, a head-up posture was associated with relatively subtle decrease in SV by only 8-14%. [8][9][10] Although the head-up posture can be considered a model of preload reduction, the expected haemodynamic consequences are insufficient to adequately evaluate the preload-reducing effect on the cardiovascular system.…”
Section: Haemodynamic Response To Postural Stressmentioning
confidence: 50%
“…Fowler's position, in which the patient's head is placed at a 45-degree angle to the table, is often used to accommodate patients comfortably (Kubota et al, 2017). This position reduces central uid volume owing to decreased venous return from the periphery, which prevents worsening heart failure (HF) (Gheorghiade et al, 2010).…”
Section: Introductionmentioning
confidence: 99%